Dampak Tik-Tok Pada Kesopanan Siswa - Paramitha, Winda Paramitha; Wardana, Mahardika Darmawan Kusuma (JURNAL PENDIDIKAN DASAR NUSANTARA, 2022)
The purpose of this study was to determine the impact of the tik-tok application on the polite character of students in one of the Ibtidaiyah madrasas located in Sidoarjo Regency. The approach used in this research is qualitative with the type of case study research. The subjects in this study were high school students at the Madrasah Ibtidaiyah where the research took place. This research was conducted in the even semester of the 2021/2022 academic year. Based on the results of the study, it was concluded that excessive use of the tik-tok application could have a negative impact on the student's character. This can be seen from the results of research which show that there are still many students who do not meet the indicators of good manners in behaving at school.